UZBEKISTAN'S TECHNOLOGICAL PRODUCTS INTRODUCTION TO THE EUROPEAN EUROPEAN MARKET STRATEGIES - Shakhnoza Ergashkhodjaeva; Khakimov Ziyodulla Ahmadovich, (Scholar Express Journals, 2022)
The article analyzes the role of Uzbekistan in the European textile market. The types of products that are relatively dominant in the competition in the textile industry of Uzbekistan are determined on the basis of the balsa index. Based on the dynamics of imported textile products from EU countries, Uzbekistan's exports are determined for a certain group of goods. The relevance and importance of the EU (EU) Special Preferences System for Sustainable Development and Good Governance (GSP +) is highlighted. The strategy of diversification of the range of products of local manufacturers of garments and knitwear to the countries of the European Union is proposed
Keywords: export; industry; textile; GSP